Dynamic Response Analysis of Floating Offshore Wind Turbines During Towing Operations - Jianan Wu; Kuankuan Wu; Liangmao Lin; Haorui Si; Binghao Zhao; Dayong Zhang (Journal of Marine Science and Engineering, 2026)
Floating offshore wind turbines (FOWTs) have become an important structural configuration for deep-water offshore wind energy development. However, existing studies have mainly focused on towing experience for conventional offshore structures and static stability assessment, while a systematic understanding of the multi-body coupled dynamic response characteristics and hazardous response factors of large-scale FOWTs under combined wind, wave, and current loads remains limited. To address the insufficient understanding of critical hazardous response indicators in existing studies, a 10 MW semi-submersible floating wind turbine was investigated in this study. Variations in environmental loads, towline constraints, and FOWT responses during towing were incorporated into a multi-body coupled analysis framework, and the key hazardous response indicators governed by different dominant environmental factors were identified. The results indicate that increasing wind speed significantly amplifies the pitch response, with the extreme pitch angle reaching approximately −7.17° under the 24 m/s wind condition. Variations in current velocity have limited influence on response amplitudes. Wave height has the most pronounced effect on heave motion and nacelle acceleration. Under the 6.5 m wave height condition, their extreme values reach approximately −1.37 m and 1.15 m/s2, respectively. Under the single-tug towing configuration, the 45° and 90° environmental directions induce pronounced lateral and yaw offsets, indicating insufficient path-keeping capability under unfavorable environmental directions. Comprehensive analysis demonstrates that pitch motion should be regarded as the primary hazardous response indicator under high wind speed conditions, while nacelle acceleration and heave motion require particular attention under high wave height conditions.